2022
DOI: 10.1186/s12917-021-03039-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical insights into the three-dimensional anatomy of cheek teeth in alpacas based on micro-computed tomography - Part 2: Maxillary cheek teeth

Abstract: Background Scientific knowledge regarding alpaca dentistry is relatively limited despite its clinical implications. The present gap in available supportive data leads to limited treatment options for dental pathology in alpacas in comparison to other species. The main goal of this study was to gain novel insights into the general and pulp morphology of maxillary cheek teeth to allow development of more advanced treatment strategies in the future. Also, the risk of causing pulp exposure when flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Hence, apical infections, previously termed tooth root abscesses, are the most common dental condition affecting alpacas, primarily involving the cheek teeth ( 1 ). Recently, micro-computed tomographic studies have confirmed that adjacent tooth roots from different cheek teeth can physically contact each other ( 7 , 8 ). However, up until now, no histological studies have been published focusing on the normal histological findings at the level of the cheek teeth in this species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, apical infections, previously termed tooth root abscesses, are the most common dental condition affecting alpacas, primarily involving the cheek teeth ( 1 ). Recently, micro-computed tomographic studies have confirmed that adjacent tooth roots from different cheek teeth can physically contact each other ( 7 , 8 ). However, up until now, no histological studies have been published focusing on the normal histological findings at the level of the cheek teeth in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The microscopical characteristics of the dental hard substances and dental and periodontal tissues were described and alpaca specific structures were identified. Referencing to specific pulp horns and root canals was based on a specific numbering system for alpaca cheek teeth ( 7 , 8 ). A classification of different types of dentin was performed based on the classification system as proposed by Dacre et al ( 11 ) in other hypsodont species.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CT has proven superior to radiography in the evaluation of dental disease in horses and is now routinely used in this species [22]. Multiple research and clinical studies have investigated CT in the evaluation of normal and abnormal dentition and other maxillary abnormalities in New World Camelids [20,21,[23][24][25]. While comparative studies in Old World Camelids are lacking to date, CT is expected to provide similar superior information to radiographs when evaluating these patients for suspected dental disease and may be considered in future clinical cases as well as research settings.…”
Section: Case Reports In Veterinary Medicinementioning
confidence: 99%